Susceptibilidade de Populações de Culex quinquefasciatus Say (Diptera: Culicidae) Sujeitas ao Controle com Bacillus sphaericus Neide no Rio Pinheiros, São Paulo - Andrade, Carlos; Campos, Jairo; Cabrini, Isaías; Filho, Carlos Marques; Hibi, Sumire (BioAssay, 2009)
Located in São Paulo city, the Pinheiros River is a large urban breed of the mosquito Culex quinquefasciatus, and such situation has been worsening since its water pumping to the Billings dam was interrupted. The local Center for Zoonosis Control launched in 2002 a new control program using chemical adulticides and a biological larvicide (Vectolex G, potency 650 BsITU/mg) based on Bacillus sphaericus. It is presented here a first evaluation on the susceptibility of C. quinquefasciatus larvae from Pinheiros River after 16 to 18 applications of Vectolex G. The mosquito susceptibility baseline to B. sphaericus was initially established for a population from an area never exposed to control (population UNICAMP, Campinas, SP). The susceptibility of two populations from the Pinheiros River (under the bridges Guido Caloi – PGUICAL and Eusébio Matoso– PEUSMAT) was accessed. Serial dilutions from 0.00312 to 0.2 mg/L from a Vectolex WDG stock solution (10,000 mg/L) were used in four replicates of 30 larvae (L3 and L4) each. The values for LC50 and LC90 to PGUICAL population are little above (respectively 2.85 and 2.66 times) and for the PEUSMAT population are close (respectively 0.60 and 1.34 times) of the values for UNICAMP population. Resistance ratios for both PGUICAL and PEUSMAT populations are in accordance to Culex populations susceptible to B. sphaericus, indicating that this larvicide could still be used.